TOR signaling system in plants (Experimental biology, 2019)
The mammalian target of rapamycin (TOR), is a protein Ser-Thr kinase that functions as a central element in a signaling pathway responsible for a cellular reaction towards stresss and nutrient/energy availability and promote appropriate changes in cell growth and proliferation, cell survival, and protein synthesis. Until now, study of the molecular mechanisms of TOR signaling pathway have been mainly focused on yeast and animal cells. As sessile organisms plants are limited to one habitat are obliged to constantly adjust the growth rates (expressed in increasing the size of organs) and development (consisting in the formation of new organs and structures) to the availability of nutrients. Furthermore, plants also overcome adverse external factors without being able to physically avoid them. Therefore, the disclosure of molecular mechanisms of the TOR signaling pathways in plants is the key to controlling stress resistance and plant productivity. Recent advances in the study of TOR signaling pathway in plants suggest a significant overlap in the cellular and developmental processes that are regulated by TOR in plants, animals and humans.The purpose of this review is to reveal the latest advances in studies of the TOR signaling pathway in plantsKey words: TOR, mammals, plants, algae, Saccharomyces cerevisiae, rapamycin, autophagy, raptor.